2016
DOI: 10.1016/j.jjie.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Green luxury goods? The economics of eco-labels in the Japanese housing market

Abstract: This paper aims to extend the existing evidence on the investment value of green buildings to international markets, specifically the residential market in Japan. Using a unique transaction database of condominiums in the Tokyo metropolitan area and a hedonic analytical framework, we find that green buildings command a small but significant premium on both the asking and transaction prices. This finding is consistent with results from other countries. As far as we are aware, this is also the first study of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 27 publications
(15 reference statements)
2
31
0
3
Order By: Relevance
“…For example, the pioneering research of Dinan and Miranowsky [52] revealed that improvements in energy efficiency applied in the real-estate market in Des Moines, Iowa, equaled a reduction in energy consumption of 1 USD (while maintaining the house at a comfortable temperature of 18 • C), which represented a market premium of 11.63 USD in price. In recent years, subsequent studies have addressed the impact of energy labelling on real-estate prices, such as the Energy Star certification [53][54][55][56], the LEED (Leadership in Energy and Environmental Design) scheme [55,56], the Energy Performance Certificates (EPC's) from the European Energy Performance of Buildings Directive [57][58][59][60][61][62][63][64], and others schemes [65], by identifying different levels in the market premiums associated with better-ranked homes. For example, the study by Bio Intelligence Service [66]-commissioned for the purpose of assessing the European Directive-reveals that the effect of each of the EPC label levels (expressed in letters) on the price ranges from 0.4% in Oxford to 11% in Vienna; it is 4.3% in Marseille, 3.2% in Lille and 2.9% in Brussels.…”
Section: The Configuration Of Real Estate Pricesmentioning
confidence: 99%
“…For example, the pioneering research of Dinan and Miranowsky [52] revealed that improvements in energy efficiency applied in the real-estate market in Des Moines, Iowa, equaled a reduction in energy consumption of 1 USD (while maintaining the house at a comfortable temperature of 18 • C), which represented a market premium of 11.63 USD in price. In recent years, subsequent studies have addressed the impact of energy labelling on real-estate prices, such as the Energy Star certification [53][54][55][56], the LEED (Leadership in Energy and Environmental Design) scheme [55,56], the Energy Performance Certificates (EPC's) from the European Energy Performance of Buildings Directive [57][58][59][60][61][62][63][64], and others schemes [65], by identifying different levels in the market premiums associated with better-ranked homes. For example, the study by Bio Intelligence Service [66]-commissioned for the purpose of assessing the European Directive-reveals that the effect of each of the EPC label levels (expressed in letters) on the price ranges from 0.4% in Oxford to 11% in Vienna; it is 4.3% in Marseille, 3.2% in Lille and 2.9% in Brussels.…”
Section: The Configuration Of Real Estate Pricesmentioning
confidence: 99%
“…Once consumer's knowledge is improved, it is hoped that it will affect consumer intention on the decision making (Rahmi et al, 2017). Today, green advertising strategy is not only conducted by the company in influencing consumer, but it is also being utilized by the government in public service advertisement for environmental issue (Fuerst & Shimizu, 2016). Apart from green advertising, the green brand image also plays an important role to influence consumer behavior (Yu-shan Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the study by Deng et al [36] is significant, showing that the green feature is less valued in the first transaction (from builder to first owner, around 4%) than in a resale (10% of the transaction value) supporting the idea that the willingness to pay varies by the transaction moment. Fuerst and Shimizu [37] estimated a green asking price premium of between 3.8% and 5.9% in housing sales in Tokyo, but they found discounts on the later transactions (the transactions after the first one) which varied depending on household characteristics and the level of maintenance costs associated with the housing design, including the energy efficiency installations. Crucially, the literature uses both asking and transaction prices depending on data availability; however, the differences in both perspectives are relevant, as the observed differences in green premium would capture the excess of housing investment to make the house more energy efficient, or the behavioral component of demand valuing the green aspects of the house.…”
Section: Literature: Green Premium Evidence and Principlesmentioning
confidence: 99%